APERFEIÇOANDO A COMUNICAÇÃO ENTRE A JUSTIÇA ELEITORAL E OS ENTES PARTIDÁRIOS MUNICIPAIS: O USO DA COOPERAÇÃO JUDICIÁRIA NACIONAL PARA SOLUÇÃO DE PROBLEMAS NA SEARA ELEITORAL - Ricardo Matos Brasileiro Filho, José; Youji Minami, Marcos; Victor Vasconcelos, Francisco; Eduardo de Oliveira Santos, César (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
Procedural communication between the Electoral Justice and municipal party branches faces significant obstacles, mainly due to recurrent outdated data in the Party Information Management System (SGIP) and the lack of standardized tools for summons and notifications. These shortcomings compromise the reasonable duration and efficiency of annual accountability processes, undermining transparency and electoral legitimacy. This study investigates whether National Judicial Cooperation can provide effective solutions to these problems without legislative amendments. The research adopts a qualitative and exploratory approach, based on bibliographic review (CPC/2015, Law No. 11,419/2006, CNJ Resolution No. 350/2020 and TSE Resolution No. 23,604/2019) and the analysis of institutional experiences. The monographic method, combined with an inductive perspective, enabled the identification of practices applicable to the electoral context. The objectives were: (i) to understand the obstacles in communication with municipal party branches; (ii) to analyze the potential of Judicial Cooperation as an integrative and efficient instrument; and (iii) to propose protocols and technological solutions to integrate party systems into the Electronic Judicial Process (PJe), ensuring greater speed and legal certainty. The results indicate that National Judicial Cooperation, supported by existing legal instruments, is a feasible path to centralize procedural communication, reduce delays and guarantee effectiveness and transparency. However, institutional, technological, and cultural barriers must be overcome. The study suggests pilot projects in Regional Electoral Courts to empirically assess the impact of the proposed measures and contribute to strengthening Brazil’s democratic system.